Investigation of Traditional Fishermen's Income in Labuhan Bilik Village, Panai Tengah District, Labuhan Batu Regency - Siregar, Zulkifli; M. Sahnan; Nasution, Atika (Asian Journal of Management Analytics, 2023)
This research aims to reveal and analyze the income of traditional fishermen in Labuhan Bilik Village. The research methods used are surveys, interviews, and data analysis. The data collected includes fishermen's income, sources of income, equipment used, and challenges faced. The research results show that traditional fishermen's income comes from several sources, including fish catches, seafood, and side jobs such as agriculture. Although fishermen's income varies throughout the year and is influenced by weather factors, fish catches remain their main source of income. The main challenges traditional fishermen face in this village include climate change, declining fish stocks, and competition with commercial fishermen. It provides a basis for developing policies that support the fisheries sector in the region.